2006
DOI: 10.1007/s00210-006-0066-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bis(maltolato) oxovanadium on experimental vascular endothelial dysfunction

Abstract: The study has been designed to investigate the effect of bis(maltolato) oxovanadium (BMOV), a protein tyrosine phosphatase inhibitor, on hypercholesterolemia and hypertension-induced vascular endothelial dysfunction. High fat diet (8 weeks) and deoxycorticosterone acetate (DOCA; 40 mg kg(-1), s.c.) were administered to rats to produce hypercholesterolemia and hypertension (mean arterial blood pressure >120 mmHg) respectively. Vascular endothelial dysfunction was assessed using isolated aortic ring preparation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…Atorvastatin was shown to improve the function of vascular endothelium by reducing oxidative stress through downregulation of NADPH oxidase [54]. In addition, atorvastatin was shown to improve the integrity of vascular endothelium [29,51]. Moreover, atorvastatin was reported to prevent the development of VED by upregulating the expression and activation of eNOS and thus increasing the generation and bioavailability of NO [55].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Atorvastatin was shown to improve the function of vascular endothelium by reducing oxidative stress through downregulation of NADPH oxidase [54]. In addition, atorvastatin was shown to improve the integrity of vascular endothelium [29,51]. Moreover, atorvastatin was reported to prevent the development of VED by upregulating the expression and activation of eNOS and thus increasing the generation and bioavailability of NO [55].…”
Section: Discussionmentioning
confidence: 96%
“…Since eNOS is a major isoform expressed in vascular endothelium, it is suggested that the endothelial protective potential of fenofibrate may be mediated through eNOS. Accumulating evidences suggest that elevation in the level of circulating lipids impair the integrity of vascular endothelium and induces VED [50,51]. It has been shown that nicotine administration alters the lipid profile by increasing the levels of TC and TG and consequently decreasing the levels of HDL [52].…”
Section: Discussionmentioning
confidence: 99%
“…The BMOVinduced inhibition of PTPase may close ATP-sensitive K + channels and consequently activate eNOS to reduce oxidative stress and subsequently improve the vascular endothelial dysfunction (104). In addition, the BMOVinduced inhibition of PTPase also improved vascular endothelial dysfunction in high fat diet-induced hypercholesterolemia (105) and deoxycorticosterone acetateinduced hypertension in rats (105).…”
Section: Effect Of Vanadium Compounds On Vascular Diseasesmentioning
confidence: 99%
“…Vanadate, a compound structurally related to BMOV, has been demonstrated to reduce oxidative stress [18]. Recently, it was reported from our laboratory that BMOV has prevented diabetes mellitus, hyperhomocysteinemia, hypertension and hypercholesterolemia-induced VED [19,20]. Uric acid has been documented to increase the generation of ROS and impair the endothelial production of NO [21][22][23].…”
Section: Introductionmentioning
confidence: 97%